The Qatar 2022 World Cup Controversy in CNN Indonesia's News Frames - Aradea Ibnu Tsabit; Razaqa Hariz; Naufal Syafi Rafif (Persepsi: Communication Journal, 2023)
The World Cup soccer event held in Qatar generated various responses from various audiences in Indonesia. This research aims to examine the direction of online media news framing in Indonesia related to the event by taking the subject at CNN Indonesia online media. The research method uses the analysis method of William A. Gamson's analysis method which includes various framing devices and reasoning devices to analyze the direction of CNN Indonesia's framing in covering the 2022 World Cup in Qatar. This paper is included in descriptive qualitative which is to find out CNN Indonesia's views factually and accurately. The object of research on the World Cup in Qatar took several news on CNN Indonesia within two months to be analyzed. The results showed that CNN Indonesia in reporting the 2022 World Cup has a perspective that is more inclined to use metaphors elements in framing devices to package interpretations of various events related to the 2022 World Cup and often uses elements of appeals to principles in reasoning devices.